RIGHTS AND OBLIGATIONS OF HUSBAND AND WIFE IN ESTABLISHING HOUSEHOLD HARMONY ACCORDING TO ULAMA SYAFI'IYAH “ CASE STUDY AT DS. SUMURBATU. KEC. MADANG CHAPTER. BOGOR REGENCY" - Ardiansyah, Sadat; Hamdani, Ikhwan; Arif, Suyud (JURNAL ILMU SYARIAH, 2023)
In a household, husband and wife have rights and obligations that must be fulfilled, because rights and obligations are an effort to create a harmonious, peaceful and peaceful household. The rights and obligations of husband and wife in the household are very important things to know, this is so that a balance is created in household life and will become a family that is sakinah, mawaddah, warahmah. The formulation of the problem in this study is: 1. What are the views of the Syafi'iyah scholars regarding the rights and obligations of husbands and wives. 2 How is the application of the rights and obligations of husband and wife in realizing household harmony in the village of Sumbatu and their suitability according to the view of the Syafi'iyah scholar (Imam Nawawi). The purpose of this study was to determine the rights and obligations of husband and wife in the household according to Syafi'iyah scholars and to find out how the rights and obligations of husband and wife are implemented in realizing household harmony in Cibarengkok village, Babakan Madang sub-district. The research method used in this writing is case study research using qualitative methods. The results of this study concluded that the rights and obligations of husband and wife cannot be separated because both of them must be balanced between rights and obligations such as the rights and obligations of a husband to his wife: to provide a living both physically and spiritually , provide education to his wife and so on, and the rights and obligations of a wife to her husband include: obedience, living in one house with her husband, not having a gloomy face and so on.